Pengaruh Variabel Terkait Email, Kepribadian Dan Demografi Terhadap Stres Kerja - Aini, Nurul; Nisa, Yunita Faela (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
This study was conducted to determine the significance of the influence of related variables email (the email work importance, email volume, email management tactics, email overload), type D personality and demographics (gender, occupation, age) against work stress. Participants in this study were employees who use email as a medium job taken with non- probability sampling technique that is convenience sampling. CFA Technique (Confirmatory Factor Analysis) was used to test the validity of measuring instruments and multiple regression analysis was used to test the research hypothesis.This research showed that is significantly related variables email, type D personality, anddemographics (gender, occupation and age) as an influence on work stress. A large proportion of thevariance of work stress described by all independent variables by 46.4%, while the remaining 53.6% isinfluenced by other variables outside of this study. There are three variables that significantly to jobstress, type D personality, gender and occupation. While the variable related to email (email workimportance, email volume, email management tactics, email overload), and age did not significantlyinfluence work stress. Researchers suggest the company should have the data of employees who havepersonality type D, in order to minimize the stress of work on employees. DOI: 10.15408/tazkiya.v22i1.8163